Estudo fitoquímico das raízes de Piper mollicomum Kunth - Jardim, Jeane Uilma Galindo (2012)
The genus Piper considered the largest in the family Piperaceae, with at least 1000 species found mainly in Asia and the New World. Yours species have several representative commercial and medical applications, being subject of several studies related to the discovery of new sources of natural active substances. Based on data described in the literature regarding the pharmacological potential of the metabolites isolated from the genus Piper, as well as the occurrence of species not yet fully exploited in terms of chemical and pharmacological, then was decided to perform the phytochemical study of the species Piper mollicomum (Kunth) aiming at the isolation and identification of chemical constituents of this species, as well as the availability of its extracts, fractions and isolated compounds for pharmacological studies. From the phytochemical study of phase dichloromethane Piper mollicomum Kunth was possible to isolate, by chromatographic methods such as column chromatography on silica and Preparative Thin Layer Chromatography, five substances, among them two isobutyl amides: 2-Propenamide, 3-(6-methoxy-1,3-benzodioxol-5-yl)-N-(2-methylpropyl)-(2E) and 2- Propenamide,3-(6- methoxy -1,3-benzodioxol-5-yl)-N-(2-methylpropyl)-(2Z) and two pyrrolidines amides: Pirrolidine, 1-[3-(6- methoxy -1,3-benzodioxol-5-yl)-1-oxo-2-propenyl-(E) and Pirrolidine, 1-[3-(6- methoxy -1,3-benzodioxol-5-yl)-1-oxo-2-propenyl-(Z) and a phenylpropanoid called a 2-Methoxy-4,5-methylenedioxypropilphenone. For structural identification of these substances were used spectroscopic methods such as IV and NMR 1H and 13C uni and two-dimensional techniques and the comparison with models data in the literature.